Comparison of different systems for purification of recombinant proteins produced by transient expression in plants - Lypova, N.M.; Sindarovska, Y.R.; Gerasymenko, I.M.; Sheludko, Y.V.; Bannikova, M.A.; Kuchuk, N.V. (Фактори експериментальної еволюції організмів, 2008)
Three different approaches for purification of transiently expressed recombinant
proteins from plants using GFP as a reporter have been successfully applied. The purification
scheme including ammonium sulfate precipitation and anion-exchange chromatography was
compared with two tag-based protocols applying metal affinity chromatography with a 6xHis
tag and intein mediated purification with a chitin-binding affinity tag. Три різних підходи для очищення рекомбінантних білків, отриманих методом
транзієнтної експресії в рослинах, було успішно застосовано з використанням GFP як
репортера. Схему очищення, яка включала преципітацію сульфатом амонію і
аніонообмінну хроматографію, порівнювали з протоколами тегового очищення з
використанням 6xHis-тега та хітин-інтеін-опосередкованого очищення. Три различных подхода для очистки рекомбинантных белков, полученных
методом транзиентной экспрессии в растениях, были успешно применены с
использованием GFP как репортера. Схему очистки, включающую преципитацию
сульфатом аммония и анионообменную хроматографию, сравнивали с протоколами
теговой очистки с использованием 6xHis-тега и хитин-интеин-опосредованной очистки.